Extension of the 5-alkynyluridine side chain via C–C-bond formation in modified organometallic nucleosides using the Nicholas reaction - Renata Kaczmarek; Dariusz Korczyński; James R. Green; Roman Dembinski (Beilstein Journal of Organic Chemistry, 2020)
Dicobalt hexacarbonyl nucleoside complexes of propargyl ether or esters of 5-substituted uridines react with diverse C-nucleophiles. Synthetic outcomes confirmed that the Nicholas reaction can be carried out in a nucleoside presence, leading to a divergent synthesis of novel metallo-nucleosides enriched with alkene, arene, arylketo, and heterocyclic functions, in the deoxy and ribo series.